Pengendali Kecepatan Motor Induksi 3-Phase pada Aplikasi Industri Plastik - Sri Hardiati; Folin Oktafiani; Joni Pristianto; Teguh Praludi; Yusuf Nur Wijayanto (INKOM Journal, 2009)
A circuit for speed controlling of three phase motor induction was designed and implemented. The circuit is using triac as main of component and supported by diac, diode, and the other passive electronics component. The result is a prototype of the speed controlling circuit. The circuit was implemented in plastic industry for keeping of the plastic yarn, so we can optimize production process and increasing the result as better quality and efficient. Keywords: control, speed , triac, motor induction